Gender perspective in Malay proverbs - Hamdan, Rahimah; M. D. Radzi, Shaiful Bahri (IDOSI Publications, 2014)
The Malay community is rich in heritage, inherited from race by succession. Proverbs, as an oral tradition, are the result of combining intellect, talent, experience, thoughts and norms held. In accordance with this deeply rooted existence within the Malay community, sayings are loaded with elements that guide the community towards a harmonious life; in accordance with particular social convention. Many gender codes have been recorded to determine the gender pattern desired by the community. Given the strength of the proverb as "a tool of social control”, this study will identify the factors that influence the construction of gender and the justification behind the picture of the gender system of society. Thus, the research methodology adopted in this paper is a textual analysis by using the collection of Malay proverbs maintained by Abdullah Hussain (2003). Indeed, it will give meaning to the concept of binary-opposition formed by Malay patriarchal hegemony using local wisdom proverbs as evidence.